1873 Nev. Comp. Laws 583, Offenses Against Public Morality, Health, and Police, § 133 - (:unkn) unknown (General Publisher, 1872)
Provided that any one who is found in possession of a firearm with intent to commit robbery shall be fined no more than 100 dollars
--
Keywords: CARRY - INTENT TO COMMIT CRIME